A longitudinal analysis of early lung function trajectory in survivors of childhood Hodgkin lymphoma. Issue 1 (27th June 2022) - Zheng, Katina; Bassal, Mylène; Mitsakakis, Nicholas; Cepalo, Tanita; Hamid, Jemila Seid; Momoli, Franco; Reisman, Joseph; Nair, Vimoj; Radhakrishnan, Dhenuka
Abstract: Background: Childhood Hodgkin lymphoma survivors suffer from long‐term effects decades after treatment completion with a prevalence of pulmonary dysfunction of up to 65.2%. Aims: This study explored the early trajectory of pulmonary function in pediatric cancer patients with Hodgkin lymphoma who received pulmonary toxic therapy. Methods and Results: In this single‐center, 20‐year retrospective cohort study, we included patients who were <18 years old at diagnosis of Hodgkin lymphoma between January 1994 and December 2014, and received bleomycin or thoracic radiation. We measured pulmonary function and reported on percent predicted values for forced expiratory volume in 1 s, total lung capacity, and diffusing capacity of the lungs. We used linear mixed models to identify the association of clinical factors with longitudinal changes in lung function at time points before and after treatment completion. Of 80 children who met inclusion criteria, all were treated with bleomycin, and 83.8% received thoracic radiation. More than half (51.2%) of patients had any abnormalities in lung function measures during the study observation period which averaged 24.2 months (±31.1SD). Females, younger age at diagnosis and treatment with radiation were associated with lower lung function measurements at various time points. While the majority of children experienced a recovery of their lung function within 1–2 years after treatment completion, some children with these risk factors did not. Conclusion: Pulmonary function abnormalities begin early in children treated for Hodgkin lymphoma. While the majority of children demonstrate a slow and continuous improvement in lung function back to baseline over time, we recommend routine asymptomatic screening of pulmonary function in certain childhood cancer survivors, particularly females, those diagnosed young and patients who received radiation therapy.